2015
DOI: 10.1063/1.4923423
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced and temporally stable field emission from MWCNTs grown on aluminum coated silicon substrate

Abstract: In this work, a detailed field emission study of multi-walled carbon nanotubes (MWCNTs) grown on Si and Al coated Si substrates is reported. Morphological and microstructural studies of the films show higher entanglement of CNTs in the case of CNT/Si film as compared to CNT/Al/Si film. Raman studies show that the defect mediated peak (D) is substantially suppressed as compared to graphitic peak (G) resulting in significant reduction in ID/IG value in CNT/Al/Si film. Field emission (FE) current density of CNT/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…6 Generally, the field emission process is a theoretical model proposed by Fowler and Nordheim, which is based on quantum mechanical tunneling. 7,8 In order to make highly performance field emission emitters having large emission current, low turn-on and threshold fields, there are two challenges to enhance field emission properties of emitters like (i) lowered work function, (ii) increased field enhancement factor of the emitters. For instance, Naik et al has reported that vertical aligned ZnO nanosheet arrays have lower turn-on field and good field emission current stability owing to increased field enhancement factor.…”
Section: Introductionmentioning
confidence: 99%
“…6 Generally, the field emission process is a theoretical model proposed by Fowler and Nordheim, which is based on quantum mechanical tunneling. 7,8 In order to make highly performance field emission emitters having large emission current, low turn-on and threshold fields, there are two challenges to enhance field emission properties of emitters like (i) lowered work function, (ii) increased field enhancement factor of the emitters. For instance, Naik et al has reported that vertical aligned ZnO nanosheet arrays have lower turn-on field and good field emission current stability owing to increased field enhancement factor.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, homogeneous solution (0.02 gm/ml) of ferrocene and xylene was prepared. The prepared solution was used for CNT growth on the silicon substrate at 730 • C in the higher zone with solution vaporizing temperature of 450 • C in the lower zone as reported earlier [37]. The grown CNT films were coated with In metal of two different thicknesses (50 nm, 100 nm) using a thermal evaporation technique at a base pressure of 5 × 10 −5 mbar.…”
Section: Methodsmentioning
confidence: 99%